EFEKTIVITAS BEBERAPA JENIS BIOINSEKTISIDA TERHADAP KEANEKARAGAMAN DAN POPULASI ARTHROPODA PADA EKOSISTEM PADI SAWAH - Andi Dian Tristiana Kusuma; Ayu Kartini Parawansa; St Subaedah (Percetakan Umi Toaha Makassar, 2019)
Bioinsecticides have the potential to affect arthropod populations in lowland rice ecosystems. The purpose of this study are 1) Knowing the effect of Beauveria bassiana, Metarhizium anisopliae and Verticillium lecanii on population and diversity of arthropods and 2) Knowing the effectiveness of giving 0.5 gram / 1.4 liter of water and 1 gram / 1.4 liter of water to each bioinsecticide on Arthropod population and diversity was carried out in Turikale District, February 2019 until April 2019. This study used a 2 factorial randomized block design. The first factor is the type of bioinsecticide and the second factor is the bioinsecticide dose of data analysis using Anova in the STAR 2.0.1 2013 program to see the average number of arthropod populations in each treatment. The results of the study showed that 1) The administration of Beauveria bassiana, Metarhizium anisopliae and Verticillium lecanii affected the population but did not affect the diversity of arthropods. 2) Each dose of 0.5 gram / 1.4 liter of water and 1 gram / 1.4 liter of water in each bioinsecticide effectively suppresses the arthropod population of the herbivorous group. Which means the use of bioinsecticides on diversity and arthropod populations in rice plants is feasible to be developed.